Hospital Management Information System in Increasing Efficiency - Andwika, Ida Bujangga; Yundari, Eli; Florenza, Yolla (LPPM STIKI Malang, 2024)
Healthcare services are the main topic because of the high complexity challenges in the health sector. The purpose of this study is to determine the implementation of Hospital Information System (HIS) in increasing the efficency of healthcare services. The research design used in this article is a literature review method related to Hospital Information Systems in supporting the efficiency of hospital services using databases. In this study, the researcher collected literature review data with a thematic structure based on the concept of thinking using the keywords